2018
DOI: 10.1259/bjr.20180367
|View full text |Cite
|
Sign up to set email alerts
|

Bi-plane and single plane angiography: a study to compare contrast usage and radiation doses for adult cardiac patients in diagnostic studies

Abstract: This is a large cohort and statistically comprehensive study comparing bi-plane and single plane coronary angiography. Other studies 4, 5, 6, 12 have used Student's t-tests to measure the difference between means, however this provides no causative information on the differences found. This study provides a view of the causative impact of bi-plane usage on DAP and contrast use via multivariate regression modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The clinical indication of the procedure can be critically reviewed and high-risk patients may benefit from more intense or prolonged postprocedural monitoring of urine output and retention parameters. Contrast media volume is a key factor for the development of CIN, especially in high-risk patients [ 34 ] and may be managed accordingly: the use of biplane angiography systems helps to reduce contrast media exposure [ 35 ]. There are technical devices which are efficient in reducing contrast media over-injection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical indication of the procedure can be critically reviewed and high-risk patients may benefit from more intense or prolonged postprocedural monitoring of urine output and retention parameters. Contrast media volume is a key factor for the development of CIN, especially in high-risk patients [ 34 ] and may be managed accordingly: the use of biplane angiography systems helps to reduce contrast media exposure [ 35 ]. There are technical devices which are efficient in reducing contrast media over-injection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] It has also been reported that biplane fluoroscopy uses less contrast dye than single-plane fluoroscopy at the expense of higher radiation dose, as two X-ray images can be acquired by the biplane system with a single injection of contrast dye. [59,60] Given that the excessive use of contrast dye is the main cause of acute kidney injury, [61,62] biplane fluoroscopy may be more appealing to patients with renal impairment, whereas single-plane imaging may be preferred by those without. In this context, future additional studies comparing the effects of biplane versus single-plane imaging by our BXI system on the overall radiation dose, contrast load, and procedural time with our microrobotic guidewire, EMA, and MSA systems simultaneously involved are worth of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of angioFFR (an earlier version of this prototype) estimated from single plane acquisitions and agreement of angioFFR and FFR have been previously reported in a study of 100 lesions in 73 patients [11], but our study expanded on these findings, as we could confirm that angi-oFFR calculated from data acquired in biplane mode yielded to similar results as those from data acquired in single plane mode. This is an important result, since many institutions routinely use biplane C-arm systems for coronary angiographic imaging [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies of angiography-derived FFR have been carried out with single plane or biplane C-arm angiography systems [6,11], but it remains unclear whether both acquisition modes yield to similar results. Biplane systems are used for coronary angiography in many institutions [14][15][16]. They offer the advantage of allowing the acquisition of two simultaneous views of a vessel during the same heartbeat, and with one contrast injection, where single plane systems require two separate contrast injections to acquire two views.…”
Section: Introductionmentioning
confidence: 99%